ChemInform Abstract: Synthesis of Neo‐Tanshinlactone via the Palladium‐Mediated Intramolecular Biaryl Coupling Reaction. Issue 18 (11th April 2013) - Abe, Hitoshi; Kawai, Toshitaka; Komatsu, Yoshinori; Kamimura, Mayu; Takeuchi, Yasuo; Horino, Yoshikazu
Abstract Starting material (II) is prepared from commercially available compounds in 12 steps.